2009
DOI: 10.1007/s12306-009-0006-6
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder prosthesis as revision surgery after fractures of the proximal humerus, treated initially by internal fixation or hemiarthroplasty

Abstract: Complex (3-4 fragments) fractures of the proximal humerus often have a bad outcome, whatever treatment is performed. When revision surgery is required, reverse shoulder prosthesis can improve function and reduce pain in these patients. We analysed whether the choice of the first treatment (hemiarthroplasty vs. reduction and fixation) can influence the outcome of revision surgery. Our data demonstrate that results are not significantly dependent on the choice of the first implant, even though there is a tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…We had used it in a previous study [15], and we confirm the reliability of this method, which is very accurate, due to the large amount of ''questions'' included.…”
Section: Discussionsupporting
confidence: 53%
“…We had used it in a previous study [15], and we confirm the reliability of this method, which is very accurate, due to the large amount of ''questions'' included.…”
Section: Discussionsupporting
confidence: 53%
“…5,17,22,[71][72][73][74][75][76] Revision was performed for failed treatment of proximal humeral fractures in patients with severe pain and loss of function. All patients treated in this way also had one or more of the following: tuberosity reabsorption, radiolucency around the humeral stem, osteoarthritis of the glenoid or a rotator cuff tear of > 2 cm.…”
Section: Revision Surgerymentioning
confidence: 99%
“…All patients treated in this way also had one or more of the following: tuberosity reabsorption, radiolucency around the humeral stem, osteoarthritis of the glenoid or a rotator cuff tear of > 2 cm. 17,71,74 In addition deep shoulder infection following surgery was described with either with a single-stage revision for infected RSR 76 or a single-or two-stage revision following infected hemiarthroplasty or rotator cuff surgery. 72 Further RSR was described after cuff failure following a total or hemiarthroplasty 5,22 and revision RSR after baseplate failure when 79% of patients (11 of 14) were managed by insertion of a larger glenosphere.…”
Section: Revision Surgerymentioning
confidence: 99%
“…Lollino et al investigated similar outcomes in patients who underwent RTSA for revision of failed shoulder hemiarthroplasty or ORIF following three-and four-part proximal humerus fractures [33]. Utilizing validated outcomes and functional testing, the authors found that while clinical outcomes were notably better following ORIF, there were significant improvements in both groups and the overall outcomes were not influenced by the initial method of surgical treatment.…”
Section: Failed Shoulder Hemiarthroplastymentioning
confidence: 99%